Menganalisis Iklim Sekolah dan Peran Keluarga dalam Mencegah Kekerasan Siswa - Masruhatul Basiroh; Cantika Adelia Fahmasari; Siti Nur Aisyah; Devy Habibi Muhammad (Pascasarjana IAI Al-Khairat Pamekasan, 2025)
This study aimed to comprehensively analyse the relationship between school climate and the role of the family in efforts to prevent violence among students. The phenomenon of student violence in educational settings was a complex problem that required multi-stakeholder intervention. A positive school climate, characterised by a sense of safety, fairness, and supportive interpersonal relationships, was hypothesised to be a key factor in reducing aggressive behaviour. Meanwhile, the role of the family as the primary socialisation environment, including parenting styles, communication patterns, and parental involvement in school activities, was crucial in instilling anti-violence values and monitoring adolescent behaviour. The research employed a qualitative approach using the library research method. Data collection was conducted through the identification and retrieval of relevant literature from various academic databases, such as Google Scholar and other scholarly sources. The findings indicated a significant correlation between an inclusive school climate and a lower incidence of student violence. In addition, the study found that active involvement and open communication between families and schools strengthened the effectiveness of prevention programmes. Families that applied an authoritative parenting style tended to have children with a lower risk of engaging in violent behaviour.